(untitled) (Research, Society and Development, 2021)
This study outlined the profile of drug treatment for patients treated at a specialized service, evaluating aspects related to adherence, adverse reactions (ADR) and drug interactions (IM), as well as the pharmacological response. The research was carried out in a specialized service located in São Miguel do Guamá-Pará, from August to September 2020, including patients who were under treatment and over 18 years old. To assess the pharmacological response, clinical aspects were considered before and after treatment. In the case of adherence, the Morisky Scale was used, the RAM, the Naranjo Algorithm and the IM were searched in specialized sites. The subjects, after treatment, had new symptoms or symptoms prior to treatment, despite being treated with 2 or more medications. Some problems were detected in this study, such as: more than 50% of patients had low adherence, had ADR and had at least one serious drug interaction. These results suggest that drug treatment may present a potential risk to the patient, requiring pharmacotherapeutic follow-up aimed at problems diagnosis of drug related problems, as well as resolving them.